Altruisme Bhakti Marga Yoga dalam Bhagavadgita - I Ketut Wisarja; Ni Nyoman Suastini; Ni Wayan Aryani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Humans as multidimensional beings, in their daily interactions with other people produce different impressions, views and conclusions from one another. Human actions or behavior in the form of social concern to provide selfless help to others have recently been felt to have faded or disappeared. Therefore, the teaching of bhakti marga yoga is actually a way or way of connecting with God through love, loving the country, loving individuals who deserve respect, loving fellow human beings, and loving the universe. That is the true truth contained in bhakti marga yoga, because this teaching immediately enjoys the fruits of religion, where love is the tool and love is the goal. This article aims to discuss and analyze various kinds of motivations for someone to provide help and their correlation with the teachings of their religion. Primarily the teachings of bhakti marga yoga in the Bhagavadgita.